Youth at risk of early leaving – A comparative view on the Romanian and German cases highlighting family circumstances and personal challenges as major risk categories and a foundation for support strategies - Miulescu, Miruna Luana [Verfasser]; Ruth, Klaus [Verfasser] (My University, 2021)
“This paper explores the importance of different parameters influencing young people’s Early Leaving of school or training (EL) in applying a five-category research framework, which includes: personal challenges, family circumstances, institutional risks, social relationships and structural risk factors. This paper compares the German and the Romanian cases of Early Leaving, focusing on personal challenges and family circumstances which are particularly salient in both countries. Despite this commonality, countries differ in terms of the national shares of youth EL. Drawn from 43 interviews and focus groups with 111 teachers and 203 young people, carried out as part of a broader European project, the identified risk factors are analysed in their interrelationships. By taking a comparative approach to considering the importance of personal and family factors for EL, the paper analyses the subcategories of risks that are important in both countries. The specific national characteristics of the school systems are taken into account in reflecting on the national rates of EL. This requires consideration of the interactions between personal challenges and family circumstances, as well as between personal and family factors and other categories of the framework. In addition, other cultural, social and political contexts are taken into account.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 2.4.1 Bildungs- und Berufswege; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); 370; 300; Schulabbruch; Jugendlicher ohne Schulabschluss; Ausbildungsabbruch; Jugendlicher ohne Ausbildungsvertrag; Einflussfaktor; Familie; Internationaler Vergleich; Rumänien; Bundesrepublik Deutschland